2011
DOI: 10.1515/jpm.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal circumference ratio for the diagnosis of intertwin birth weight discordance

Abstract: By comparing EFWs, 59.5-71.4% of discordant pairs >25% are missed, whereas an AC ratio >1.3 would identify almost all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…They found that an AC ratio of ≥1.3 was the best prediction of severe BW discordance. 8 In this recent study, these findings could not be confirmed. However, when using a cut-off of 1.2 in our study, severe BW discordance was seen significantly more often compared with the group with an AC ratio less than 1.2 (16.7% vs 0.8%, p < 0.01).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…They found that an AC ratio of ≥1.3 was the best prediction of severe BW discordance. 8 In this recent study, these findings could not be confirmed. However, when using a cut-off of 1.2 in our study, severe BW discordance was seen significantly more often compared with the group with an AC ratio less than 1.2 (16.7% vs 0.8%, p < 0.01).…”
Section: Discussionmentioning
confidence: 59%
“…Because it has been thought that EFW discordance is not very accurate in predicting BW discordance, other methods have been sought. According to Simoes et al ., the AC ratio (calculated as the AC of the larger twin divided by AC of the smaller twin) alone predicts BW discordance better than the EFW discrepancy. They found that an AC ratio of ≥1.3 was the best prediction of severe BW discordance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also wonder about the best cut-off of EFW difference to describe severe discordance. As EFW is a poor predictor of discordance (because of the ± situation that exists [4,5]), one should aim for a higher value (i.e. 25%-30% difference) to avoid over diagnosis.…”
mentioning
confidence: 99%